THE EFFECT OF NICKEL ADDITION ON THE MECHANICAL PROPERTIES WELDED JOINTS OF LOW CARBON STEEL - Susetyo, Ferry Budhi; Sari, Yunita; Setiawidi, Yoganantya (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2021)
The SMAW process is a commonly used metal joining method because it is very practical in its use, less cost, and easy availability of equipment. The SMAW process is also easy to operate and can be used in all welding positions. The problem that often occurs in steel construction lies in the welded joints. Therefore, it is necessary to increase the mechanical properties by adding nickel(Ni) to the welded joints. In this research,  electrodes E 6013 and steel of ASTM A 36 was used. The tensile tests, bending tests, hardness tests, macrostructure, and microstructure will be carried out to see changes in mechanical properties. The addition of Ni contributes well to mechanical properties. The tensile strength, face bending, side bending, and hardness increased by 27.6%, 14.5%, 4.8%, and 20.9%, respectively. In the observation of the macrostructure, the porosity was not visible in all samples, while in the microstructure observation, ferrite and pearlite phases were formed in all samples.